Copper tolerance of Aegilops, Triticum, Secale and triticale seedlings and copper and iron content in their shoots - Bálint, András Ferenc; Kovács, Géza; Sutka, József (Acta Biologica Szegediensis, 2002)
Twenty-seven different cereal accessions belonging to the Triticinae subtribe were screened for copper tolerance in hydroponic cultures. Based on the shoot dry mass reduction and the decreased value of the FJFm fluorescence induction parameter the Secale species were the most tolerant ones. Slightly tolerant and relatively sensitive common wheat cultivars were also identified. No significant correlation was found between the copper and iron concentration of the shoots and the degree of tolerance.